The Efficacy of Pharmacological Interventions in Pulmonary Arterial Hypertension (WHO Group 1): A Systematic Review of Randomized Controlled Trials - Daniel France Risa H; David Kevin Graham Lesnussa (International Medical Journal Corp. Ltd, 2025)
Introduction: Pulmonary arterial hypertension (PAH), WHO Group 1, is a progressive vasculopathy leading to right heart failure and premature death. Pharmacological therapies targeting the endothelin, nitric oxide, and prostacyclin pathways have improved outcomes, but the optimal treatment strategy remains a subject of ongoing investigation. This systematic review synthesizes evidence from randomized controlled trials (RCTs) to evaluate the efficacy of these interventions, with a focus on the comparative benefits of monotherapy versus combination therapy. Methods: A systematic search of MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov was conducted for RCTs published from January 1990 to the present. Studies enrolling adult patients with WHO Group 1 PAH and evaluating approved pharmacological agents against placebo or another active therapy were included. Data on study design, patient characteristics, and a minimum of 15 predefined outcomes—including functional, hemodynamic, biomarker, and clinical event endpoints—were extracted. Methodological quality was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool. A narrative synthesis was performed. Results: Seventeen pivotal RCTs were included in the final analysis. Monotherapy with endothelin receptor antagonists (ERAs), nitric oxide pathway modulators (phosphodiesterase-5 inhibitors and soluble guanylate cyclase stimulators), and prostacyclin pathway agents demonstrated significant improvements over placebo in exercise capacity (e.g., 6-minute walk distance), hemodynamic parameters (e.g., pulmonary vascular resistance, cardiac index), and functional class. Intravenous prostacyclins were unique in demonstrating a mortality benefit in a standalone RCT. Landmark event-driven trials established the superiority of combination therapy. The AMBITION trial showed that upfront dual combination therapy with ambrisentan and tadalafil reduced the risk of clinical failure by 50% compared to pooled monotherapy, primarily by reducing PAH-related hospitalizations. Sequential add-on therapy yielded mixed results, with some combinations showing benefit (e.g., sildenafil added to epoprostenol in PACES) while others did not meet their primary endpoint (e.g., bosentan added to sildenafil in COMPASS-2). Discussion: The evidence base for PAH treatment is robust, demonstrating a clear paradigm shift from sequential monotherapy to upfront combination therapy for most patients. The superiority of initial dual combination with an ERA and a PDE-5 inhibitor is well-established for delaying disease progression. The evolution of clinical trial endpoints from the 6-minute walk distance to composite morbidity/mortality outcomes reflects a more clinically meaningful assessment of therapeutic benefit. Conclusion: Pharmacological interventions have significantly improved the prognosis for patients with PAH. The current evidence strongly supports initial, risk-stratified treatment with upfront dual combination therapy to delay clinical worsening. Intravenous prostacyclins remain a critical component of therapy for high-risk patients. Future research should focus on direct comparisons of combination strategies and the role of initial triple therapy.